Contextos ambientais de terras indígenas na fronteira do Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The general objective of this research was to analyze the environmental contexts of indigenous lands in the Cerrado domain in light of the advance of capitalist relations of production, especially in the agribusiness and mining sectors. To achieve this objective, qualitative and quantitative data from institutions such as the Brazilian Institute of Geography and Statistics (IBGE), the National Indian Foundation (FUNAI), the Indigenous Missionary Council (CIMI), the National Institute of Colonization and Agrarian Reform (INCRA), and MapBiomas, among others, were used. These data were organized into maps, graphs and tables. The results show that indigenous lands located in the states of Mato Grosso and Mato Grosso do Sul suffer more direct effects from the presence of agribusiness, the areas converted to agriculture and pasture are larger, as well as the use of pesticides, irrigation pivots and conflicts over land rights, especially in Mato Grosso do Sul. In Tocantins, Goiás, and Maranhão agribusiness is not as expressive as in the other states in relation to the proximity to indigenous lands. Mining is more present in the north of Goiás and in the center of Tocantins, in this context there are mining processes overlapping indigenous lands and/or being installed in rivers that pass through these lands, which can compromise the quality and even the availability of water for these populations. In the state of Maranhão, agriculture and cattle-raising are not significantly present within the limits of indigenous lands, but may expand in the coming decades. In general, it is evident that the agribusiness sector produces more conflicts in Mato Grosso and Mato Grosso do Sul, mining has a greater presence in Goiás and Tocantins. In Maranhão there are high rates of deforestation and illegal logging. It is worth mentioning that these activities do not occur in isolation and that as a whole they present a serious threat to the ecologically balanced environment and to the exclusive usufruct of indigenous peoples of their lands.
Keywords: Terras Indígenas; Cerrado; Agronegócio; Mineração; Indigenous lands; Cerrado; Agribusiness; Mining; CIENCIAS HUMANAS::GEOGRAFIA